The Use of Asynchronous Google Classroom with Video Teaching Tutorial on Improving Student Writing Achievement for Recount Text at Public Senior High School 6 Kendari - Nggawu, La Ode; Alam, R. (Journal of Applied Science, Engineering, Technology, and Education, 2022)
This study aims to investigate how effective asynchronous Google classroom with VTT on improving students' writing achievement for recount text at SMAN 6 Kendari used quantitative design with pre-experimental one group pre-test and post-test. The research population was 346 entire school who registered in academic year 2020/2021. Meanwhile, XI MIPA 3 were 28 students as a valid sample of this study. Sampling selected using simple cluster random. Data collection used a written test that analyst by paired sample t-test that shows descriptive and inferential statistics based on students pre-and post-test. The research finding shows that there was significant different in gain score for pre-test (M=62,50; SD= 5.853) and Post-test (M=80.1071; SD=5.09422), t (27) = 13.095; p < 0.05, ttable= 2.052. It shows t-count > t-table with sig α < 0.05, H0 is rejected and H1 is accepted, so it can be concluded that using asynchronous google classroom with video teaching tutorial show a positive effect on student writing achievement for recount text at SMAN 6 Kendari.